Analisis Mutu Bakso Ikan Home Industri dan Komersil Di Babakan Raya Bogor - Stevy Imelda Murniati Wodi; Eko Cahyono; Nurfaida Kota (Universitas Sriwijaya, 2019)
Fish balls is a food product that popular and favored by children or adult. Fish balls usually produced as a home industry or commercial product. The aims of this research are to figure out the quality of the home industry or commercial fish ball at Babakan Raya Bogor. This research using a descriptive method. The best score for home industry category, water content analysis for sample A (51.20%), ash analysis for sample A (2.13%), for commercial category, the best fat content is for sample A (0.27%), protein content is for sample A (12.52%) and for carbohydrate by difference is for sample A (18.62%).